THE EFFECT OF ADDING PETROFISH PROBIOTICS TO FEED AT DIFFERENT DOSES ON THE GROWTH AND SURVIVAL OF BARRAMUNDI (Lates calcarifer) JUVENILES - Relita, Relita; Juliana, Juliana; Tuiyo, Rully (Asian Journal of Aquatic Sciences, 2023)
This study aimed to determine the effect of adding Petrofish probiotics to feed at different doses on the growth and survival of barramundi (Lates calcarifer) juveniles. The research utilized an experimental method with 120 barramundi juveniles as test subjects, distributed into treatments A (Control), B 10mL/kg dosage), C (15mL/kg dosage), and D (20mL/kg dosage). The study was conducted for 30 days, using 12 buckets containing ten barramundi juveniles. The research employed a Completely Randomized Design (CRD) with Analysis of Variance (ANOVA), followed by Least Significant Difference (LSD) post hoc tests. The results indicated significant effects for each treatment. The highest absolute weight and length were observed in treatment D at 0.90 g and 0.73 cm, followed by treatment C at 0.77 g and 0.67 cm, treatment B at 0.69 g and 0.62 cm, and the lowest values were in treatment A at 9.51 g and 0.58 cm.